49.6k views
5 votes
-3-(7x+5)+9x=x-8+3x+10

User Hagne
by
4.9k points

2 Answers

6 votes
-3-(7x+5)+9x=x-8+3x+10

-3-7x-5+9x=x-8+3x+10

-3-5+9x-7x=x+3x-8+10

-8+2x=4x+2

-8-2=4x-2x

-10=2x

X=-5
User Stonedauwg
by
5.2k points
5 votes
X should equal -5.
Steps: Distribute , combine like terms, isolate the variable, and then divide.
-3-(7x+5)+9x=x-8+3x+10-example-1
User Harunahi
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.